MATING AND OVIPOSITION IN CASSIDA INDICOLA DUVIVIER (COLEOPTERA: CHRYSOMELIDAE). - SINGH, J.P.; SIDHU, PARAMPAL KAUR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The mating and oviposition of Cassida indicola Duv. was studied in the laboratory at 28*+2° C temperature and 70-80% relative humidity. Mating begins a week after the emergence of adult females. Each mating process takes 35-45 minutes. Oviposition occurs three days after copulation. In total 50-55 eggs are laid by a single female during its ovipositional period of 20-22 days. The eggs are laid singly, or in pairs.